Fatores intervenientes no contato pele a pele entre mãe e bebê na hora dourada - Monteiro, Bruna Rodrigues (2019)
The golden hour is defined as the first after birth hour and is a crucial moment to identify maternal and neonatal risk, as well as the implementation of evidence-based practices for proper care, including skin-to-skin contact between mother and child. This practice, recommended by protocols of good obstetric practice, is sometimes considered fragmented; either by maternal or neonatal complications and above all, by institutional routines. In this scenario, this study aimed to analyze the factors that interfere with skin-to-skin contact between mother and child in the golden hour. This is a cross-sectional observational study with a quantitative approach. The research was conducted at Leide Morais Maternity Hospital and Ana Bezerra University Hospital, both references in the usual risk delivery in the state of Rio Grande do Norte. The sample consisted of 105 parturient admitted to the prepartum, labor and after birth sectors, based on the following eligibility criteria: gestational age> 37 weeks; usual-risk pregnant women who were on the verge of vaginal delivery. Data collection took place from May to July 2019, through a structured instrument based on scientific literature and governmental recommendations, totaling 36 questions. For analysis, data were entered into a database and analyzed quantitatively by descriptive and inferential statistics using the Statistical Package for Social Sciences version 18. The significance level adopted was 5% with a 95% confidence interval. The study was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte under number 3,187.28. The study found that, of the 63 deliveries observed at Leide Morais maternity and 42 deliveries observed at Ana Bezerra, the beginning of immediate contact was favored by an obstetrician in 59% (62) labors and interrupted by pediatricians in 81% (85). Regarding the factors responsible for delayed contact, 6.7% (7) of the neonates experienced complications, while 5.7% (6) underwent procedures before contact, and procedures/maternal complications were absent during this period. While the factors responsible for contact interruption were observed in 67.6% (71) of cases, due to procedures in neonates, followed by complications in the child 15.2% (16). In the follow-up, the result showed that the contact occurred immediately after normal delivery in 85.7% (90) of the cases, the longest skin- to-skin contact durability was recorded between one and five minutes of life of the newborn in 82.9% (87) and only three (2.8%) neonates experienced the golden hour. The study identified that, in the health services analyzed, the skin- to-skin contact between mother and baby in the golden hour, occurred for only three binomials, unlike the others who were interrupted by hospital conduct.